2022
DOI: 10.1094/pdis-12-21-2790-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium annulatum Associated with Young Vine Decline in California

Abstract: From 2018 to 2021 a decline was detected in young vineyards of both wine and table grape (Vitis vinifera L.) in seven counties across California (Kern, Monterey, Napa, Sonoma, Tulare, Yolo, and Yuba). Affected vines showed poor or no growth throughout the season, dieback, sap exudation and internal cankers around the graft union. Lack of feeder roots was detected, indicating weak root development. In some cases, graft failure was associated with the symptomatology in recently established vineyards (<3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Seventeen different Fusarium species have been isolated and identified from asymptomatic and symptomat-ic grapevines (Highet and Nair, 1995;van Coller, 2004;Chehri, 2017;Kraus et al, 2019;Bustamante et al, 2022;Li et al, 2023). The present study identified F. oxysporum, F. proliferatum, F. ramigenum, and a potentially novel Fusarium sp., from young and mature grapevines with GTDs symptoms, from vineyards in BC, Canada.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Seventeen different Fusarium species have been isolated and identified from asymptomatic and symptomat-ic grapevines (Highet and Nair, 1995;van Coller, 2004;Chehri, 2017;Kraus et al, 2019;Bustamante et al, 2022;Li et al, 2023). The present study identified F. oxysporum, F. proliferatum, F. ramigenum, and a potentially novel Fusarium sp., from young and mature grapevines with GTDs symptoms, from vineyards in BC, Canada.…”
Section: Discussionmentioning
confidence: 64%
“…Studies from different countries have continued to report Fusarium spp. as prevalent in roots, cordons, and/or trunks of grapevines showing decline symptoms (Ziedan et al, 2011;Abdullah et al 2015;Chehri, 2017;Bustamante et al, 2022;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, keanumycin A is extremely effective in inhibiting Botrytis cinerea (MIC = 69 nM / 80 μg L –1 ), which is a devastating phytopathogen that causes Botrytis blight, also known as gray mold, in over 1000 plant species and was ranked as the second most important plant-pathogenic fungus . To a lesser extent, it also inhibited the growth of Alternaria solani, the causative agent of early blight in tomatoes and potatoes, but not of Fusarium annulatum, which can infest different fruits , and is additionally an opportunistic human pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…Fusarium annulatum is a morphologically and phylogenetically diverse species which has been recently demonstrated as distinct from F. proliferatum [ 19 ]. F. annulatum is a member of the FFSC, which has been recorded as a pathogen on more than 200 plant hosts primarily in subtropical countries [ 11 , 19 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%